2018
DOI: 10.3389/fendo.2018.00564
|View full text |Cite
|
Sign up to set email alerts
|

Association Between SLC30A8 rs13266634 Polymorphism and Risk of T2DM and IGR in Chinese Population: A Systematic Review and Meta-Analysis

Abstract: Introduction: Published data regarding the association between solute carrier family 30, member 8 (SLC30A8) rs13266634 polymorphism and type 2 diabetes mellitus (T2DM) and impaired glucose regulation (IGR) risks in Chinese population are in-consistent. The purpose of this meta-analysis was to evaluate the association between SLC30A8 rs13266634 and T2DM/IGR in a Chinese population.Material and Methods: Three English (PubMed, Embase, and Web of Science) and three Chinese databases (Wanfang, CNKI, and CBMD databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Moreover, zinc is essential for the process of insulin maturation to secretion and SLC30A8 gene- located in secretory granules of insulin, plays an important role in zinc transportation to the container vesicles of insulin. After non-synonymous polymorphism in SLC30A8 rs13266634, a newly formed amino acid (arginine) affects its regular function and puts down the formation and secretion of insulin, which lowers the amount of insulin in the body as a whole [ 27 , 28 ]. From our study, we observed a strong association of rs13266634 in our population to develop T2DM ( p < 0.0001, 0.001, <0.0001, and <0.0001; aOR = 2.08, 2.08, 4.18, and 5.97, respectively in allele, dominant, recessive, and homozygote model) and a similar association was reported in several meta-analyses for Asian and European population [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, zinc is essential for the process of insulin maturation to secretion and SLC30A8 gene- located in secretory granules of insulin, plays an important role in zinc transportation to the container vesicles of insulin. After non-synonymous polymorphism in SLC30A8 rs13266634, a newly formed amino acid (arginine) affects its regular function and puts down the formation and secretion of insulin, which lowers the amount of insulin in the body as a whole [ 27 , 28 ]. From our study, we observed a strong association of rs13266634 in our population to develop T2DM ( p < 0.0001, 0.001, <0.0001, and <0.0001; aOR = 2.08, 2.08, 4.18, and 5.97, respectively in allele, dominant, recessive, and homozygote model) and a similar association was reported in several meta-analyses for Asian and European population [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eighth member of solute carrier family 30 ( SLC30A8 ) or Zinc transporter 8 ( ZNT8 ), mainly expressed in beta cells of pancreatic islets, a novel ZNT family member which responsibly transports zinc into insulin-containing granules from the cytoplasm and subsequently forms insulin crystal for secretion, maturation and storage [ 27 ]. At 325 position, rs13266634 of SLC30A8 gene forms tryptophan (W) in the place of arginine (R) (Arg325Trp) after polymorphism that may be correlated with impaired glucose regulation [ 28 ]. Investigations have provided evidence of the association between SLC30A8 gene variants and the risk of T2DM and cardiovascular complications [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, SLC30A8 is the only candidate gene that has been linked to human T2D in genetic studies and is therefore the most promising target for a therapeutic intervention ( Table 1). Research on ZnT8 is ongoing; since 2018, multiple studies regarding T2D susceptibility in different populations have been published, highlighting the critical role of this zinc transporter in the onset of human diseases (Ding et al, 2018;Dong et al, 2018;Li et al, 2018;Lin et al, 2018;Liu et al, 2018;Plengvidhya et al, 2018). Further studies are needed to finally verify whether increased or decreased transporter activity is linked to human T2D, and therefore whether inhibition or rather activation of the transporter is required to counteract disease development.…”
Section: Solute Carrier 30: the Zinc Transporter Familymentioning
confidence: 99%
“…Previous studies have reported that the SLC30A8 (solute carrier family 30 member 8) rs13266634 polymorphism in the major C allele was strongly associated with the risk of T2DM. 60,61 In addition, Chang et al also reported that the SLC30A8 rs13266634 SNP was associated with age as a T2DM risk factor. 196 SLC30A8 is expressed in pancreatic β-cells and encodes a zinc transporter.…”
Section: Slc30a8mentioning
confidence: 99%